Identifying Stress Landscapes in Boston Neighborhoods - F. Garrett Conyersm MD, MPP; Helene M Langevin MD; Gary J Badger MS; Darshan H Mehta MD, MPH (SAGE Publishing, 2018)
Background Chronic stress plays a role in the development of health disparities. However, the relationship between neighborhood stressors and stress-related health problems and behaviors is unknown. In the city of Boston, Massachusetts, 3 neighborhoods, while within a 3 mile radius, have widely divergent life expectancies. This work aims to investigate and compare perceived neighborhood-level stressors, stress-related negative behaviors, and stress-related health problems in these neighborhoods. Methods Three hundred twenty-six participants were surveyed from the neighborhoods. Participants were asked to rate (1) 27 neighborhood stressors, (2) 16 stress-related negative behaviors, and (3) 13 stress-related health problems using a 1 to 5 Likert-type scale. Differences in responses between neighborhoods were analyzed using Kruskal-Wallis and χ 2 tests. Results The highest neighborhood stressors overall were related to finance, unequal treatment, and unsafe bike/pedestrian access. The highest stress-related health problems were related to substance abuse and obesity, and the largest stress-related behaviors were related to poor diet, intolerance, and aggressive driving. There were significant differences across neighborhoods ( P  < .05) for 18 of the 27 neighborhood stressors, 8 of the 10 stress-related health problems, and 12 of the 15 stress-related behaviors. Conclusions There is marked contrast in stress landscapes between the 3 neighborhoods in Boston despite their geographical proximity. This finding potentially serves as an explanation for the drastic differences in health outcomes, even though these neighborhoods are equidistant from academic medical centers. Strategies for improving the health of individuals should incorporate the unique stressors at the neighborhood level. Further research is needed to investigate how specifically neighborhood stressors influence the health of residents, thereby informing what policy interventions might be useful.